VIRAL VS. BACTERIAL PNEUMONIA IN CHILDREN UNDER TWO: DIAGNOSTIC CHALLENGES AND TREATMENT APPROACHES (International journal of medical sciences, 2026)
Viral and bacterial pneumonia are major causes of morbidity among infants and toddlers and are often difficult to distinguish clinically. We conducted a prospective observational study of 98 children (0–24 months) admitted with suspected pneumonia to Fergana City Children's Hospital between January 2022 and June 2025. Clinical features, chest imaging, rapid viral testing, C-reactive protein (CRP) and procalcitonin (PCT) levels, point-of-care lung ultrasound, treatments, and outcomes were recorded. Viral pathogens (RSV, influenza) were detected in 44 cases (44.9%); clinicians assigned bacterial etiology in 28 cases (28.6%). Complete recovery occurred in the majority; however empirical antibiotic use was common. PCT and combined diagnostic approaches improved bacterial prediction versus clinical features alone. Integrating rapid viral tests, selective biomarkers, and ultrasound into clinical pathways may reduce unnecessary antibiotic exposure in regional settings.